1997
DOI: 10.1073/pnas.94.24.12869
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion of alkylpurine-DNA-N-glycosylase in mice eliminates repair of 1, N 6 -ethenoadenine and hypoxanthine but not of 3, N 4 -ethenocytosine or 8-oxoguanine

Abstract: It has previously been reported that 1,N 6 -ethenoadenine (A), deaminated adenine (hypoxanthine, Hx), and 7,8-dihydro-8-oxoguanine (8-oxoG), but not 3,N 4 -ethenocytosine (C), are released from DNA in vitro by the DNA repair enzyme alkylpurine-DNA-N-glycosylase (APNG). To assess the potential contribution of APNG to the repair of each of these mutagenic lesions in vivo, we have used cell-free extracts of tissues from APNG-null mutant mice and wild-type controls. The ability of these extracts to cleave defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(91 citation statements)
references
References 33 publications
5
84
0
2
Order By: Relevance
“…For example, Roth and Samson found that myeloid progenitor bone marrow cells from Aag (Ϫ/Ϫ) mice were less MMS-sensitive than corresponding cells from wild type animals, whereas other groups found that Aag (Ϫ/Ϫ) ES cells and MEFs were more MMS-sensitive or Me-lex-sensitive than Aag (ϩ/ϩ) counterparts (23,37,48,49). The results described here reveal that the ␤-pol expression status of cells can be a variable in the MMS-sensitivity phenotype upon Aag gene deletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Roth and Samson found that myeloid progenitor bone marrow cells from Aag (Ϫ/Ϫ) mice were less MMS-sensitive than corresponding cells from wild type animals, whereas other groups found that Aag (Ϫ/Ϫ) ES cells and MEFs were more MMS-sensitive or Me-lex-sensitive than Aag (ϩ/ϩ) counterparts (23,37,48,49). The results described here reveal that the ␤-pol expression status of cells can be a variable in the MMS-sensitivity phenotype upon Aag gene deletion.…”
Section: Discussionmentioning
confidence: 99%
“…mediated by a similar phenomenon. Clearly, spontaneous generation of Aag substrates does not lead to lethality in mice, since Aag (Ϫ/Ϫ) mice are viable and are without an obvious phenotype (23,37). We therefore bred a colony of ␤-pol (ϩ/Ϫ) / Aag (Ϫ/Ϫ) mice to determine if genetic loss of Aag would rescue the ␤-pol (Ϫ/Ϫ) -associated lethality.…”
Section: Aag Is Required To Initiate Ber Of Mms-and Mnng-induced Lesimentioning
confidence: 99%
“…Here, we used molecular beacon-based DNA glycosylase assay to test whether the inhibition of ANPG by ⑀C residues could occur in cultured mammalian cells. ANPG is the only known Hx-DNA glycosylase in mammalian cells (20,45); therefore, inosine-FD oligonucleotides allow us to measure its activity with high specificity. The fluorescent oligonucleotide (35F-control) without a quencher residue, control non-modified oligonucleotide (35FD-control), and inosine-FD were delivered into human HeLa cells (Fig.…”
Section: Fig 2 Analysis Of Anpg⅐⑀c Interactionmentioning
confidence: 99%
“…(45,46) Using cell-free extracts and synthetic oligonucleotides/modified DNA, ANPG was shown to be the primary glycosylase excising eA, 1,N 2 -eG, 3mA and Hx. (46)(47)(48) Such analysis provides an unambiguous means for the designation of the substrate specificity and for the exploration of backup activities for the missing enzyme. Biologically, however, it is surprising that these knockout mice did not show any overt phenotypic abnormalities (45,46) or significant increase in the spontaneous mutation rate, even increased mutations were observed in the hprt gene of the T lymphocytes of ANPG À/À mice treated with methyl methanesulfonate.…”
Section: Author Proofmentioning
confidence: 99%
“…It is puzzling, though, that the increased levels of adducts were not paralleled by the increased incidence of liver tumors in these mice. (49) Interestingly, even though no other glycosylase activity against eA was detected using the in vitro approach, (46,47) one study reported that there was residual repair of eA adducts in the ANPG À/À mice. (50) Whether this residual activity is from another DNA glycosylase or from other repair pathway(s) remains to be determined.…”
Section: Author Proofmentioning
confidence: 99%